Unionizing High Tech: Opportunities and Obstacles. Issue 3 (August 2023) - Sheehan, Patrick; Williams, Christine L.
The WERN report documents the rise of worker-led collective action in the tech industry. We distinguish two types of activism emerging from tech professionals—demands for greater corporate social responsibility and demands for improved employment rights—and consider the opportunities each affords the larger labor movement. In the second section, we consider how the venture-capital funding model that structures the tech industry presents unique challenges to traditional union-organizing campaigns.